The Contribution of Environmental CSR to Sustainability in the Energy Sector: A Study on PT Pema Global Energi - Era Pamadia; Agus Satory (Green Publisher Indonesia, 2025)
This study aims to analyze the role of environmental Corporate Social Responsibility (CSR) implemented by PT Pema Global Energi in supporting environmental sustainability and community welfare in North Aceh. This study uses literature analysis methods, case studies, and evaluation of empirical data from the implementation of corporate CSR programs, such as land rehabilitation, waste management, and energy efficiency. The results of the study show that the company's CSR programs have a significant positive impact, including improving soil quality, biodiversity conservation, and reducing carbon emissions through environmentally friendly technology. In addition, community involvement through environmental training and programs has succeeded in increasing local awareness and capacity in environmental conservation. The conclusion of this study is that the implementation of CSR integrated with a sustainable business model not only contributes to environmental conservation, but also strengthens the company's relationship with the surrounding community. The main recommendations are to improve public education, establish strategic partnerships, and invest in innovative technologies to expand the impact of CSR programs.